Struktur Kebahasaan Bahasa Indonesia sebagai Rujukan Penggunaan Bahasa (Semantik) - Mayani Mayani; Rahmaasharihamzah Rahmaasharihamzah; Muh. Ibnu Sina (Lembaga Pengembangan Kinerja Dosen, 2025)
Semantics is a branch of linguistics that studies meaning in language, both at the word, phrase, and sentence levels. This study covers the relationship between linguistic signs and the meaning they contain and their implications for human understanding. This study aims to describe (1) the definition of semantics according to experts, (2) types of meaning in Indonesian, (3) forms of meaning change, and (4) the phenomena of ambiguity, homonyms, homophones, and homographs along with examples. This study uses a qualitative approach with a literature study method, namely examining various sources of literature such as books, journals, and scientific articles that are relevant to the study of semantics. The results of the study show that the types of meaning in Indonesian include lexical, grammatical, referential, non-referential, denotative, and connotative meanings. Changes in meaning are divided into generalization, specialization, amelioration, pejoration, and associative. In addition, linguistic phenomena such as ambiguity (double meanings due to sentence structure), homonyms (words with the same pronunciation and spelling, different meanings), homophones (same pronunciation, different spelling and meanings), and homographs (same spelling, different pronunciation and meanings) were also found.